Dusty galaxies in the Epoch of Reionization: simulations. Issue 1 (22nd March 2018) - Behrens, C; Pallottini, A; Ferrara, A; Gallerani, S; Vallini, L
Abstract: The recent discovery of dusty galaxies well into the Epoch of Reionization (redshift z > 6) poses challenging questions about the properties of the interstellar medium in these pristine systems. By combining state-of-the-art hydrodynamic and dust radiative transfer simulations, we address these questions focusing on the recently discovered dusty galaxy A2744_YD4 ( z = 8.38, Laporte et al.). We show that we can reproduce the observed spectral energy distribution (SED) only using different physical values with respect to the inferred ones by Laporte et al., i.e. a star formation rate of SFR = 78 M_ yr^-1, a factor ≈4 higher than deduced from simple SED fitting. In this case, we find: (i) dust attenuation (corresponding to τV = 1.4) is consistent with a Milky Way (MW) extinction curve; (ii) the dust-to-metal ratio is low, f d ∼ 0.08, implying that early dust formation is rather inefficient; (iii) the luminosity-weighted dust temperature is high, T_d=91± 23 K, as a result of the intense (≈100 × MW) interstellar radiation field; and (iv) due to the high T d, the Atacama Large Millimeter/submillimeter Array Band 7 detection can be explained by a limited dust mass, M d = 1.6 × 10 6 M⊙ . Finally, the high dust temperatures might solve the puzzling low infrared excess (IRX) recently deduced for high- z galaxies from the IRX–β relation.